The Bodily and the Divine: Study of a 10th Century Hindu Temple in Rajasthan, India. Issue 1 (March 2021) - Patel, Tina; Angne Alfaro, Sarah M.; Swaranjali, Pallavi
The Hindu temple is a place where gods may be approached, and divine knowledge discovered. The design of the temple based on the cosmic man, the " vastu purush mandala, " allows the experiencing body to be aligned with celestial elements, obtaining harmony with the cosmos. Exploring the sequence and processes of bodily engagement as one progresses from the periphery to the core, the article seeks to apprise designers on the rituals encompassed in worship at a Hindu temple. The article creates a mosaic of hybrid fragments via photographs, drawings, and text to emphasize the intertwining of the bodily and divine.